Behavioral manifestations of peer exclusion among three-to-five year-old children - Calderon, Paolo Mikael B.; Larracas, Ronald M.; Ugaddan, Miriam I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2020)
The study aims to describe the behavioral manifestations of peer exclusion among three-to five-year-old children. In addition, the study attempts to determine whether there are differences in behavioral manifestations based on the children's sex or age. To achieve this, the participants would have been from a progressive preschool in Quezon City due to the mixed grouping of boys and girls and the play-based, flexible daily routine. A class of 17 children, with nine males and eight females, from this school were chosen as research participants for the study. Through naturalistic observation, the researchers may be able to determine and differentiate if the variables, age or sex, have an effect on peer exclusion. However, due to the COVID-19 pandemic, classes were cancelled and the continuation of the study was put on hold. With this, the researchers highly recommend that future researchers test this thesis using similar conditions as stated in this study. In addition, the researchers also recommend that the consideration of the safety of the children and of the people involved must be prioritized before undertaking the study.
Thesis Classification: F
Thesis
Includes bibliographical references and appendices.
Keywords: Children -- Conduct of life; Peer pressure in children -- Philippines